Therapeutic Collaboration in Career Construction Counseling: Case Studies of an Integrative Model - Silva, Filipa; Taveira, Maria do Céu; Cardoso, Paulo; Ribeiro, Eugénia; Savickas, Mark L. (Frontiers in Psychology, 2022)
The mapping of therapeutic collaboration throughout counseling deepens our understanding of how the helping relationship fosters client change. To better understand the process of career construction counseling, we analyzed the therapeutic collaboration on six successful face-to-face cases. The participants were six Portuguese adults, five women and one man, real clients of a career counseling service, and four psychologists, three female and one male trained in the career intervention model. The participants completed demographic questions and measures of career certainty, vocational identity, career indecision and psychological functioning. The Therapeutic Collaboration Coding System was used to track collaboration throughout all interactive episodes. The clinical significance of the intervention was calculated by analyzing pre-post-test statistical differences for each case, with the Reliable Change Index and Z score. The findings evidenced a pattern of therapeutic collaboration evolution for good outcome cases. Based on this pattern, we propose a model of process-outcome evolution for the three phases of career construction counseling.